The Effect of Cone Drill Training on Improving Dribbling Skills and Agility in Soccer Players from Sumber Jaya, Bengkulu City - Aryo Setiawan; Ajis Sumantri; Asnawati Asnawati (Educative Sportive, 2026)
This study aims to determine the effect of cone drill training on improving the dribbling skills and agility of soccer players from Sumber Jaya, Bengkulu City. The research method used was an experimental method with a one-group pretest-posttest design. The population in this study consisted of all soccer players from Sumber Jaya, Bengkulu City, while the sample comprised 25 players selected using total sampling. The instruments used were a dribbling skills test and an agility test. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using a Paired Sample t-Test at a significance level of α = 0.05. The results showed that the average dribbling ability improved from 22.68 seconds in the pretest to 18.79 seconds in the posttest. The t-test results showed a calculated t-value of 2.497, which was greater than the critical t-value of 2.063, with a significance level of 0.000 < 0.05. Meanwhile, the average agility score increased from 11.42 seconds in the pretest to 9.29 seconds in the posttest. The t-test results showed that the calculated t-value of 2.540 was greater than the critical t-value of 2.063, with a significance level of 0.000 < 0.05. The results indicate that cone drills have a significant effect on improving the dribbling skills and agility of soccer players from Sumber Jaya, Bengkulu City. Based on the research findings, it can be concluded that cone drills are an effective training method for improving soccer players’ dribbling skills and agility. Therefore, coaches can incorporate cone drills into their regular training programs to enhance player performance.